Construção de equipamento de tratamento de superfície a plasma com fonte DC pulsada para tratamento de nitretação iônica. - Cruz, Daniel (2017)
Surface treatment techniques such as plasma aided nitriding, although very well consolidated in the industry, must still be studied well and improved. Based on this idea and with the objective of looking for better treatment conditions, this work presents the development, construction and commissioning of a reactor for plasma treatment and treatment of plasma nitriding of P-20 steel samples.The reactor was constructed in order to improve conditions for thermochemical treatment and for this purpose a chamber of stainless steel AISI 316L was built as thermochemical treatments are carried out at a very high temperature (above 500ºC). Other equipments such as Vacuum System, Power Source (Direct Current and Pulsed Direct Current), Thermocouple, Manometer, Valves and a meter for gas flux were also attached to the system. After making the equipment, it was commissioned to verify its stability. Parameters such as pressure and tension were analysed together with their influences on temperature. Five nitriding treatments were executed on this equipment in the following way: One treatment was executed during the commissioning, two of them evaluated the treatments by DC tensions and finally 2 more tested Pulsed DC treatments. Treated samples were characterized by Micro Hardness Vickers, Metallography, SEM and EDS. It was observed that treatment tension and pressure affect the temperature stabilization time and the highest temperature it can reach. Treated samples during the commissioning phase have shown edge effect. Samples treated with DC tension show non uniform treated layers. Samples treated with Pulsed DC present highly uniform layers of nitrites both in microstructure and thickness. It can be concluded, however, that the equipment shows high efficiency and serves very well for what it was built for and that, for plasma nitriding treatment, it presents much better performance with Pulsed Direct Current.